Critiquing Global Priorities: The UN Military Spending, Peacebuilding, and the Role of Love in International Relations. - Okpevra, Uwomano Benjamin (JPW (Jurnal Politik Walisongo), 2024)
This paper delves into the intricate relationship between international relations and government budgets, focusing on the paradoxical allocation of resources to both peace and war efforts. By examining the stark contrast between the colossal military expenditures of nations, particularly the United States, and the comparatively modest budgets of global peace-building institutions like the United Nations, the study sheds light on the values and priorities of international actors. It critically evaluates the consequences of this imbalance, such as unmet societal needs, and highlights the stark juxtaposition of rhetoric about democracy and the reality of military power projection. Furthermore, this paper explores the notion that the values of a nation can be better understood through its budget than its constitution, emphasising how the allocation of resources reflects a nation's true priorities. The work advocates for a shift away from viewing humanity through a security lens, and for a more compassionate approach to global issues, grounded in the politics of love and an understanding of the genuine dilemmas of humanity. Ultimately this paper contends that a recalibration of budgetary allocations and the promotion of love and compassion are vital steps toward redefining the principles that guide international relations.Keywords: Global Priorities, Politics of Budget, Paradox of Peace and War, Role of Love, Peacebuilding, UN Military Spending.